Ruairí Ó Brádaigh : The Life and Politics of an Irish Revolutionary - White, Robert W. (Robert William), 1958- (Book collections on Project MUSE., 2020)
"Since the mid-1950s, Ruairi O Bradaigh has played a singular role in the Irish Republican Movement. He is the only person who has served as Chief of Staff of the Irish Republican Army, as president of the political party Sinn Fein, and to have been elected, as an abstentionist, to the Dublin parliament. Today, he is the most prominent and articulate spokesperson of those Irish Republicans who reject the peace process in Northern Ireland. His rejection is rooted in his analysis of Irish history and his belief that the peace process will not achieve peace, but rather, will support the continued partition of Ireland and result in continued, inevitable, conflict." "The child of Irish Republican veterans, O Bradaigh has led IRA raids, been arrested and interned, escaped and been "on the run," and even spent a period of time on a hunger strike. An articulate spokesman for the Irish Republican cause, he has at different times been excluded from Northern Ireland, Britain, the United States, and Canada. He was a key figure in the secret negotiation of a bilateral IRA-British truce. His Notes on these negotiations offer special insight to the 1975 truce, the IRA ceasefires of the 1990s, and the current peace process in Ireland." "O Bradaigh has been a staunch defender of the traditional Republican position of abstention from participation in the parliaments in Dublin, Belfast, and Westminster. When Sinn Fein voted to recognize these parliaments in 1970, he led the walkout of the party convention and spearheaded the creation of Provisional Sinn Fein. He served as president of Provisional Sinn Fein until 1983, when he was forced from the position by his successor, Gerry Adams. In 1986, with Adams as its president, Provisional Sinn Fein recognized the Dublin parliament. O Bradaigh led another walkout and later became president of Republican Sinn Fein, a position he holds to this day."--Jacket.